Knowledge, attitudes and practices toward artificial intelligence among pediatricians in India: A cross-sectional web-based nationwide survey - Manasvi Tyagi; Rohit Ravi; Suchetha Sudesh Rao; Nutan Kamath; Santhosh T. Soans (PLoS ONE, 2025)
Background Artificial intelligence (AI) is rapidly advancing in healthcare and has the potential to transform patient care. This study aimed to assess the knowledge, attitudes, and practices (KAP) regarding AI among pediatricians in India. Methods A cross-sectional, web-based nationwide survey was conducted, with participants recruited via pediatric WhatsApp groups between 23 March, 2024 to 1 April 2024. A validated 25-item questionnaire, comprising multiple-choice, open-ended, yes/no, and five-point Likert scale questions, was administered using Google Forms. Descriptive statistics were used to summarize responses. Results A total of 116 pediatricians participated in the survey. The calculated sample size for the study was 114. As we had 116 responses on day 10, the survey was withdrawn accounting to a response rate of 6.7%. Most participants (91.4%) understood the concept of AI; however, only 33.6% were familiar with AI applications in pediatric practice. The majority (83.6%) anticipated the integration of AI in pediatrics within the next decade, and 90.5% expressed interest in learning more about AI applications. Notably, 25.9% reported concerns regarding AI use, and 48.3% perceived their workplaces as currently not adequately equipped to implement AI tools. Commonly used AI tools included ChatGPT, Canva AI, Neonatal AI, Google AI, Trusted Computing Base (TCB), and Voicera. Conclusion While awareness of AI and its potential impact was high, knowledge and formal training were limited. Nevertheless, there was considerable enthusiasm among pediatricians to acquire further knowledge and adopt AI applications in their practice.